Advanced tissue technologies of blood-brain barrier organoids as high throughput toxicity readouts in drug development - Luisa Bell; Claire Simonneau; Chiara Zanini; Elena Kassianidou; Christelle Zundel; Rachel Neff; Bernd Steinhuber; Marco Tecilla; Alex Odermatt; Roberto Villaseñor; Nadine Stokar-Regenscheit (Heliyon)
Recent advancements in engineering Complex in vitro models (CIVMs) such as Blood-brain barrier (BBB) organoids offer promising platforms for preclinical drug testing. However, their application in drug development, and especially for the regulatory purposes of toxicity assessment, requires robust and reproducible techniques. Here, we developed an adapted set of orthogonal image-based tissue methods including hematoxylin and eosin staining (HE), immunohistochemistry (IHC), multiplex immunofluorescence (mIF), and Matrix Assisted Laser Desorption/Ionization Mass Spectrometry Imaging (MALDI-MSI) to validate CIVMs for drug toxicity assessments. We developed an artificial intelligence (AI) algorithm to increase the throughput and the reliability of histomorphologic evaluations of apoptosis for in vitro toxicity studies. Our data highlight the potential to integrate advanced morphology-based readouts such as histological techniques and digital pathology algorithms for use on CIVMs, as part of a standard preclinical drug development assessment.